2020
DOI: 10.1093/bib/bbaa079
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targets and signaling mechanisms of vitamin C activity against sepsis: a bioinformatics study

Abstract: Sepsis is a life-threatening complication of pneumonia, including coronavirus disease-2019 (COVID-19)-induced pneumonia. Evidence of the benefits of vitamin C (VC) for the treatment of sepsis is accumulating. However, data revealing the targets and molecular mechanisms of VC action against sepsis are limited. In this report, a bioinformatics analysis of network pharmacology was conducted to demonstrate screening targets, biological functions, and the signaling pathways of VC action against sepsis. As shown in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 46 publications
(44 reference statements)
1
52
0
Order By: Relevance
“…In agreement with GO analysis, KEGG pathway enrichment analysis also showed that the therapeutic effects of vitamin C on CVD were mainly associated with the JAK-STAT signaling pathway, as well as the PD-1 pathway, EGFR tyrosine kinase inhibitor resistance, the FoxO signaling pathway, and the chemokines signaling pathway ( Li et al, 2020a ; Li et al, 2020b ). There is crosstalk among STAT, PD-1, EGFR, and FoxO signals.…”
Section: Discussionsupporting
confidence: 67%
“…In agreement with GO analysis, KEGG pathway enrichment analysis also showed that the therapeutic effects of vitamin C on CVD were mainly associated with the JAK-STAT signaling pathway, as well as the PD-1 pathway, EGFR tyrosine kinase inhibitor resistance, the FoxO signaling pathway, and the chemokines signaling pathway ( Li et al, 2020a ; Li et al, 2020b ). There is crosstalk among STAT, PD-1, EGFR, and FoxO signals.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, vitamin C deficiency in critically ill patients is associated with increased vasopressor requirements, multi-organ failure and increased mortality [ 69 ]. Vitamin C has an anti-sepsis effect by reducing inflammatory response and oxidative stress as well as suppressing immunological dysfunction, which are the main pathophysiological mechanisms of sepsis [ 70 ]. Pre-clinical evidence showed that vitamin C supresses excessive cytokine release leading to sepsis-induced organ dysfunction [ 67 ].…”
Section: The Role Of Vitamin C In Management Of Ards Sepsis Septic mentioning
confidence: 99%
“…Sepsis is essential a type of in ammatory disease, in which the involvement of multiple players is required [7,8]. With the increased elucidation of the molecular mechanism of sepsis, some molecular factors, such as ALK, have been proven to be potential targets for the development of novel therapies against sepsis and sepsis-induced organ failures, such as targeted therapy to treat sepsis by regulating regulated gene expression [9,10]. However, to date, effective targets for sepsis targeted therapy remain lacking.…”
Section: Introductionmentioning
confidence: 99%